2019
DOI: 10.2478/midj-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Unpaid Reviews made by Renowned Vloggers: the Case of Smartphones

Abstract: The main aim of the study is to establish the effects of online unpaid reviews posted by internet celebrities (renowned vloggers) on audience’s purchase intention, product recommendation and engagement on the platform. The empirical research conducted for this purpose revealed that audience’s attitude towards the vlogger is positively affected by the perceived attributes of the vlogger - trustworthiness, expertise and attractiveness. Further, the attitudes towards the vlogger reflect on the attitudes towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This was also considered positive by the audience. It was in line with [22] who stated that perception was influenced by the attitudes towards the vlogger and the product.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This was also considered positive by the audience. It was in line with [22] who stated that perception was influenced by the attitudes towards the vlogger and the product.…”
Section: Resultssupporting
confidence: 80%
“…Based on these considerations, there has been no research that uses sentiment codes to express consumer perceptions and attitudes towards electronic product reviews developed through the Nvivo method and internet ethnography. In addition, current research on attitudes towards electronic products is only limited to certain products, for example [22] only used smartphone products. The difference is, this research seeks to reveal the audience's perceived attitudes and buying interest in electronic products reviewed online via YouTube channels through sentiment codes and internet ethnography and pragmatics.…”
Section: Figure 1 Social Media Rankmentioning
confidence: 99%
“…Trust is defined as a 'perceived credibility and benevolence of a target of trust (i.e., the other party)' (Doney & Cannon, 1997). Alternatively, trust is the perceived honesty, reliability, and capacity of the source to provide impartial information (Moldovan & Ciornea, 2019;Roy, 2006). In the context of celebrity or spokesman, prior literature has considered celebrity characteristics in determining consumer's attitudes and purchase decisions (Awasthi & Choraria, 2015;Bergkvist & Zhou, 2016).…”
Section: Trust On Vlogger Recommendation (Tvr)mentioning
confidence: 99%
“…Vloggers share a few characteristics with bloggers, the main difference is the medium of sharing of the content such as bloggers post content in the written form compared to vloggers who share the content through videos (Fisalbon, 2019), also referred to as video bloggers (Ladhari et al, 2020). Vloggers often become internet celebrity and share their views and experiences related to brands and often act as indirect brand ambassadors (Moldovan & Ciornea, 2019). Vloggers frequently share daily life events, activities, opinions, and preferences on SNS, often engaging in two-way interaction with their followers and hence become opinion leaders (Casaló et al, 2008; Djafarova & Trofimenko, 2019; Sokolova & Kefi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…R4: Do consumer attitudes toward the video content affect consumer attitudes toward the X70 brand model?Other than that,Lu et al (2014) studied Taiwanese blogs and found highly positive attitudes toward sponsored recommendation posts, which improves purchase intention. In the other work byMoldovan and Ciornea (2019), consumer attitude towards vloggers and products is significantly related to actions on YouTube to recommend the product. On that account, this study proposed to scrutinise the social media engagement intentional behaviour measurement into more detailed segments as inCao et al (2021).…”
mentioning
confidence: 99%